2018
DOI: 10.3846/jcem.2018.3068
|View full text |Cite
|
Sign up to set email alerts
|

System Dynamics Model Based on Evolutionary Game Theory for Quality Supervision Among Construction Stakeholders

Abstract: To address the gap, that is, few studies have explored the influence of the participants’ interactions with one another during construction quality supervision, this paper proposes a system dynamics model based on evolutionary game theory to describe the complex and dynamic interactions among tripartite stakeholders in China, including the project owner (PO), construction supervising engineer (CSE), and construction contractor (CC). First, the replicated dynamic equation set is established in terms of expense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…Several attempts by researchers as well as project professionals to tackle the effect and causes of delays in construction project have not met the positive results needed as Asadi et al (2018) suggests. Guo et al (2018) concluded on his study conducted in Ankara Turkey that, delay could occur in the preconstruction stage described as the beginning to the stage of contract signing between the client and the contractor, but many construction projects delay in the stage of the construction. Al-Agele et al (2016) also said industry of construction is one that involves dynamic and complex process.…”
Section: B Managing Delays In Construction Projectsmentioning
confidence: 99%
“…Several attempts by researchers as well as project professionals to tackle the effect and causes of delays in construction project have not met the positive results needed as Asadi et al (2018) suggests. Guo et al (2018) concluded on his study conducted in Ankara Turkey that, delay could occur in the preconstruction stage described as the beginning to the stage of contract signing between the client and the contractor, but many construction projects delay in the stage of the construction. Al-Agele et al (2016) also said industry of construction is one that involves dynamic and complex process.…”
Section: B Managing Delays In Construction Projectsmentioning
confidence: 99%
“…Compared with the traditional game theory, ET combines concepts from biology, evolution, nonlinear dynamics, and game theory with dynamic evolutionary process analysis. It was developed to overcome the disadvantages of the traditional game theory when analyzing the bounded rationality of players and dynamic process of game playing [25]. Each player chooses among alternative actions or behaviors whose payoff or fitness depends on the choices of others [26].…”
Section: Evolutionary Game Theorymentioning
confidence: 99%
“…Among the experience and performance, top management competence, project factor, supply chain and leadership, availability of resources and effective cost control measures, they ranked the top management competency highest. Guo, et al [29], validated the project performance difference between non-supervised project and supervised project by engineer using evolutionary game theory. They recommended that the compulsory supervision is effective way to control project performance.…”
Section: Strategies To Mitigate Project Delaysmentioning
confidence: 99%